2004
DOI: 10.1136/fn.89.1.f51
|View full text |Cite
|
Sign up to set email alerts
|

Associations between perinatal interventions and hospital stillbirth rates and neonatal mortality

Abstract: Background: Previous studies suggest that high risk and low birthweight babies have better outcomes if born in hospitals with level III neonatal intensive care units. Relations between obstetric care, particularly intrapartum interventions and perinatal outcomes, are less well understood, however. Objective: To investigate effects of obstetric, paediatric, and demographic factors on rates of hospital stillbirths and neonatal mortality. Methods: Cross sectional data on all 65 maternity units in all Thames Regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 18 publications
1
22
1
1
Order By: Relevance
“…During the last decade lay campaigners have sought to persuade the NHS that birth is a natural process that requires minimal medical intervention. Highlighting the risks of childbirth has been politically unfashionable and there has been little recognition at a political level of the link between safe childbirth and the availability of obstetricians [13,14]. Further, it is possible that analysis of intrapartum deaths might raise the issue of inadequate staffing levels in our labor wards -a major concern for practising midwives and obstetricians.…”
Section: Intrapartum Stillbirthsmentioning
confidence: 99%
“…During the last decade lay campaigners have sought to persuade the NHS that birth is a natural process that requires minimal medical intervention. Highlighting the risks of childbirth has been politically unfashionable and there has been little recognition at a political level of the link between safe childbirth and the availability of obstetricians [13,14]. Further, it is possible that analysis of intrapartum deaths might raise the issue of inadequate staffing levels in our labor wards -a major concern for practising midwives and obstetricians.…”
Section: Intrapartum Stillbirthsmentioning
confidence: 99%
“…[9][10][11] The role of ethnicity is more complex as some ethnic groups have other risk factors for neonatal death such as low socioeconomic status, smoking or consanguinity. 12 There are conflicting data on indigenous/ aboriginal populations in Australia with reports of both higher risk of neonatal death 13 and no excess risk.…”
Section: Introductionmentioning
confidence: 99%
“…Obstetric studies [6,7] have indicated that excess and potentially preventable neonatal deaths may happen 'out of hours' when staffing levels are lower. Adult ICU studies have related the level and type of consultant input to outcome [8,9].…”
Section: Introductionmentioning
confidence: 99%